2020
DOI: 10.3390/genes11040366
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Transcriptomic Analysis Identified Novel Putative Cassava lncRNAs Involved in Cold and Drought Stress

Abstract: Long non-coding RNAs (lncRNAs) play important roles in the regulation of complex cellular processes, including transcriptional and post-transcriptional regulation of gene expression relevant for development and stress response, among others. Compared to other important crops, there is limited knowledge of cassava lncRNAs and their roles in abiotic stress adaptation. In this study, we performed a genome-wide study of ncRNAs in cassava, integrating genomics- and transcriptomics-based approaches. In total, 56,840… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…LncRNAs work as cis -acting elements near the RNA synthesis sites ( Zhao et al, 2020b ). Further, trans -acting factors, they can also work away from synthesis sites ( Suksamran et al, 2020 ). LncRNAs transcribed by polymerase II, III, IV, and V. They are further divided into five categories depending on their positions in genome near or away from protein-coding genes.…”
Section: Mechanismmentioning
confidence: 99%
“…LncRNAs work as cis -acting elements near the RNA synthesis sites ( Zhao et al, 2020b ). Further, trans -acting factors, they can also work away from synthesis sites ( Suksamran et al, 2020 ). LncRNAs transcribed by polymerase II, III, IV, and V. They are further divided into five categories depending on their positions in genome near or away from protein-coding genes.…”
Section: Mechanismmentioning
confidence: 99%
“…LncRNAs can act as key genetic and epigenetic regulators of gene expression (Karlik et al, 2019). They may function as cisacting elements by working near the site of RNA synthesis, acting directly on consecutive genes on the same strand (Zhao et al, 2020; Figure 1A); or as trans-acting factors by operating far from the site of synthesis (Suksamran et al, 2020; Figure 1B). LncRNAs may interfere with the binding of transcription factors to promoter regions (Csorba et al, 2014).…”
Section: Lncrnas As Precursors In Rddm Silencing Pathwaymentioning
confidence: 99%
“…The lncRNA TahlnRNA27 was induced under heat treatment and characterized as putative miRNA precursor by presenting Ta-miR2010 family sequences (Xin et al, 2011). Similarly, 182 novel cold-responsive lncRNAs are known to be differentially expressed in cassava (Suksamran et al, 2020); whereas 2,271 lncRNAs were cold-responsive in alfalfa (Zhao et al, 2020).…”
Section: Lncrna In Crop Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that csd1, csd2 and ccsmutanten showed a higher heat stress tolerance than wild-type plants, combined with an increased accumulation of heat stress transcription factors and heat shock proteins as well as much less damage to plants (Guan et al, 2013). Corn (Yu et al, 2018) and cassava (Suksamran et al, 2020) responds to abiotic stress such as heat, cold, salt, and drought.…”
Section: Cold and Heat Stress Tolerancementioning
confidence: 99%